Synthesis of Ion Imprinted Polymers (IIPs) Adsorbent Materials Using Fe(III) Leaching Process with Variation of Hydrochloric Acid Solvent Concentration and Heat Treatment - Royani, Idha; Maimunah; Edianta, Jaya; Alfikro, Ihsan; Fiber Monado; Jorena; Satya, Octavianus Cakra; Virgo, Frinsyah (Science and Technology Indonesia, 2024)
Fe(III)-IIPs material was prepared using a cooling-heating method with different leaching variations. The synthesis process used several chemical components, including EGDMA, MAA, and BPO as the crosslinker, functional monomer, and initiator. This study focused on the template formation process of IIPs with leaching variations, using parameters such as molarity concentration, solution mixture, and temperature to influence the amount of template formed in the polymer body. The spectra of XRD showed a widening value of FWHM as higher molarity was applied during the leaching process, with the widest one at 0.163 rad for IIPs 3 M. Fe(III) peak is located at 680-610 cm−1 or 1386-1350 cm−1 within the unleached sample, according to FTIR spectra. It also can be traced at minimum intensity in leached samples. SEM data processing showed that higher concentrations were essential in releasing Fe(III) ions from the polymer body. Meanwhile, heat treatment did not strongly impact the template formation sites of IIPs. Synthesized Fe(III)-IIPs materials had adsorption capacity, optimum time, and efficiency of 9.35 mg.g−1, 40 minutes, and 93.48%, respectively. Based on the results, Fe(III)-IIPs materials had great potential as adsorbents for removing metal pollutants from water.